2016
DOI: 10.1007/s12221-016-5879-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature pyrolysis on jute fibers as a thermochemical modification method

Abstract: 250, 300 o C was conducted in order to remove non-cellulosic compounds without damaging the structure of the cellulose in jute fibers. The chemical, morphological, and mechanical aspects of prepared low-temperature pyrolyzed jute fibers were investigated by Fourier transform infrared (FTIR) spectroscopy, the wettability test in water/dichloromethane system, moisture content measurement, X-ray diffraction (XRD) analysis, scanning electron microscope (SEM), and tensile test using universal testing machine (UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The morphological aspects showed that low-temperature pyrolysis of the jute fiber improved the interfacial bonding of the jute fiber and the ASKLTPU matrix. The removal of non-cellulosic compounds by the low-temperature pyrolysis was expected to increase the interfacial bonding between the JF and the ASKLTPU matrix, as shown in polypropylene (PP) composites with PJFs [30].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The morphological aspects showed that low-temperature pyrolysis of the jute fiber improved the interfacial bonding of the jute fiber and the ASKLTPU matrix. The removal of non-cellulosic compounds by the low-temperature pyrolysis was expected to increase the interfacial bonding between the JF and the ASKLTPU matrix, as shown in polypropylene (PP) composites with PJFs [30].…”
Section: Resultsmentioning
confidence: 99%
“…As a modification method, low-temperature pyrolysis of jute fiber was performed according to the previous work [30]. Jute fiber was put into the laboratory muffle furnace (LT3/11/P330, Nabertherm GmbH, Liliental, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations